Problemas familiares asociados al cáncer hereditario - Cortés-funes, Fabiola (Psicooncología, 2005)
Hereditary cancer represents a real challenge for the multidisciplinary sanitary team that has to manage it. The Genetic Counselling Unit takes care not only for the oncology patient but also for his/her healthy relatives. Therefore, it is important to have the suitable tools to evaluate the whole family; the Family System Illness Model and the genogram are used to draw the map to ascertain what is happening inside the family and be able to set out the intervention according to the characteristics of the family system.